Wearable Energy Harvester: Application of Piezoelectric Sensors in Shoes as a Portable Power Source - Moch. Rizqi Aulia Islami; Mohammad Zafari; Saqib Anjum (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the effect of variations in pressure loading on piezoelectric sensors mounted on shoes on the amount of electrical power generated and to compare the performance of series and parallel circuit configurations in real-time energy harvesting applications. Methodology: This study used an experimental method with a ceramic piezoelectric sensor (2 cm diameter), a digital multimeter, a shoe insole, a 100 µF 25 V capacitor, a 1N4002 diode, connecting cables, and a soldering tool. Data were collected with variations in body weight (52.65 kg–72.65 kg) and gait speed (normal walking, fast walking, running) for 2 km for series and parallel configurations. Main Findings: The results showed that the greater the pressure due to body weight, the higher the electrical power generated. The series circuit produced a maximum power of 3.39 µW, while the parallel circuit reached 51.2 µW at varying weights. At varying speeds, running produced the highest power, with a maximum of 42.56 mW in the parallel configuration. This demonstrates that circuit configuration and pressure significantly influence power output. Novelty/Originality of this study: This research presents a wearable prototype that integrates piezoelectric sensors, shoe design, and a power storage system for real-time energy harvesting. Unlike previous research limited to simulations, this study demonstrates a functional prototype capable of charging low-power devices, thus supporting sustainable energy technologies and developing the application of piezoelectric principles to portable energy sources.